2011
DOI: 10.1007/s11243-011-9547-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of a dioxo-molybdenum(VI) complex anchored on TiO2 for the photochemical oxidative decomposition of 1-chloro-4-ethylbenzene under O2

Abstract: The catalytic activity of dioxo-molybdenum(VI)-dichloro[4,4 0 -dicarboxylato-2,2 0 -bipyridine] covalently anchored through the carboxylate function to the surface of TiO 2 has been tested for the oxidative degradation of 1-chloro-4-ethylbenzene in MeCN solution under argon and UV irradiation (k = 254 nm). After 4-5 h of photochemical reaction, the Mo complex was reoxidized in the presence of O 2 in the dark, and then the reaction was continued under argon. The reaction proceeds by the intermediate formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Среди современных разработок наиболее перспективными с экологической точки зрения считаются процессы деструктивного окисления ядохимикатов в жидкой фазе, где в качестве окисляющих агентов используют кислород [6][7][8], озон, пероксид водорода и др. Однако в случае ДДТ необходимо активирующее воздействие на реакционную систему.…”
Section: հ ա յ ա ս տ ա ն ի գ ի տ ո ւ թ յ ո ւ ն ն ե ր ի ա զ գ ա յ ի ն ...unclassified
“…Среди современных разработок наиболее перспективными с экологической точки зрения считаются процессы деструктивного окисления ядохимикатов в жидкой фазе, где в качестве окисляющих агентов используют кислород [6][7][8], озон, пероксид водорода и др. Однако в случае ДДТ необходимо активирующее воздействие на реакционную систему.…”
Section: հ ա յ ա ս տ ա ն ի գ ի տ ո ւ թ յ ո ւ ն ն ե ր ի ա զ գ ա յ ի ն ...unclassified
“…These natural systems, known as molybdenum-enzymes, are the source of inspiration to synthesize different complexes called “biomimetics” that have allowed an advance in the understanding of the molecular oxygen activation mechanisms (Dupé et al, 2015; Heinze, 2015). Adapting these natural systems into analogous bio-inspired complexes, several structures of Mo VI O 2 with a variety of ligands have been synthesized and evaluated in OAT processes for substrates such as alkanes, alkenes, and phosphines (Bakhtchadjian et al, 2011; Kück et al, 2016). Recently, the photocatalytic activity of some dioxo-molybdenum complexes supported on different supports as metal-organic framework (MOF) or inorganic oxides as TiO 2 or SiO 2 were assessed in the selective epoxidation of terpenes as α - and β -pinene or limonene, using molecular O 2 as the primary oxidizing agent (Castellanos et al, 2012, 2013; Martínez et al, 2018, 2020, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This property has allowed us to study the coordination sphere effect in the reactivity of the Mo = O entity (Kühn et al , 2000; Günyar et al , 2009). We have reported, over the years, the synthesis of several complexes with bypiridil ligands and studied, under homogeneous and heterogeneous conditions, their properties as oxygen atom transfer agents (Paez et al , 2008; Arzoumanian et al , 2010; Castellanos et al , 2012) Their ability to participate in catalytic oxidation has been reported in the selective oxidation of phosphines, arylalkanes and the photochemical oxidative decomposition of persistent organic pollutants (POPs) specifically using molecular O 2 as oxygen atom donor under visible light irradiation (Paez et al , 2009; Bakhtchadjian et al , 2011; Castellanos et al , 2013). In this work we report the synthesis and results on the molecular characterization (FTIR, NMR) and X-ray powder diffraction data for the compound dichlorodioxido (4,4-dimethoxycarbonyl-2,2-bipyridyl) molybdenum(VI).…”
Section: Introductionmentioning
confidence: 99%